NEWLY-GRADUATED INDONESIAN MEDICAL DOCTORS PERCEPTION TO INDONESIAN INTERNSHIP PROGRAM - Suryatma, Anton; Despitasari, Mieska; Sulistioratih, Erni Endah; Herryanto, Dwi; Dianawatisari, Heni (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
This manuscrip present the perceptions from intern doctors regarding their abilities, confidence and experience. A mailing survey was conducted with the question of how respondents would perceive if they did not undergo the internship program. Analysis using simple bivariate logistic regression. The results there were 6830 responden, Average ability= 6.31 Confidence=6.27 dan Experience=5.95. 46.8% of respondents felt they had abilities, 47.5% felt confident and 54.6% had experience without having to participate in an internship program The variable that statistically significantly affects the perception of ability is gender (Man p <0.01 OR=0.679 95%CI=0.612-0.754), while for self-confidence also gender (Man p <0.01 OR=0.667 95%CI=0.601-0.741); Experience (Man p <0.01 OR=0.721 95%CI=0.650-0.799) Conclusion. Perception of newly graduated doctors almost same beetween the groups that feel capable, confident and have experience and the group without having to go through the internship process. Suggestions need to be done cost benefit studies to assess whether the internsip program is useful for all parties.